Appendix 4.8: Marcos Diary Entry, 18 September 1971 - Philippine Journal of Third World Studies, Kasarinlan (Kasarinlan: Philippine Journal of Third World Studies; Vol 27, No 1-2-Vol 28, No 1-2 (2012-2013): Marcos Pa Rin! The Legacy and the Curse of the Marcos Regime, 2017)
Marcos here lists his enemies, making it seem that he is embattled on all fronts—members of the media, communists and communist front organizations, and members of the military who “are not enthusiastic about the suspension of the privilege of the writ,” and chastises the people for their lack of vocal opposition to (communist-led) revolution. Then, Justice Fred Ruiz Castro seems to indicate that the Court might not be in his favor.